PRODUCTION COSTS: CONCEPTUAL ASPECTS OF DOMESTIC AND INTERNATIONAL EXPERIENCE IN ACCOUNTING REFLECTION - Тюхтій, М. В.; Пономаренко, О. Г. (Scientific Progress & Innovations, 2014)
Full recognition, distribution and registration reflection overhead cost has a direct impact on the reliability of the determination of cost, which correlates with indicators of enterprise performance. Methodological difficulties for practicing accountant is the process of attributing overhead costs to fixed and variable, since this division in some situations a conventional signs. The same applies to the determination of "normal capacity". Domestic and foreign research and development of the abovementioned issues relating primarily base choosing the optimal allocation of overhead costs. Research conducted towards comparative analysis of different options cost allocation bases and their adaptation to the specific manufacturing process in specific sectors of the economy. Attention is also provided technical approaches include overheads in cost of sales in terms of its definition of the norms P (S) BU 16 «absorption cost» and according to popular in developed foreign countries approach «direct-costing», as well as in light of the requirements of the tax legislation.